REFLEXIONS ON A MASSIVE OPEN ONLINE COURSE ‘ACADEMIC WRITING’ - May-Melendez, Rosa; Ferrer-Méndez, Rafael; Pacheco-Balám, Gina; Sánchez, Alma (European Scientific Journal, ESJ, 2015)
As part of the different strategies implemented to improve students’ abilities in English, professors from the Universidad Autónoma del Carmen (UNACAR) in Mexico added a Massive Open Online Course (MOOC) in one of the English courses. This MOOC called ‘Principles of Written English 1’ was focused on essay development, grammatical correctness, and selfediting. The purpose was also to investigate a different learning setting and students’ performance on online courses. In order to gather data, researches designed a weekly reflection sheet where students were asked to provide their reflexions about the course and the difficulties or novelties found during this workshop. After the analysis of the information, researchers noticed that students are not interested towards online courses because they do not usually take formal online lessons. However, the study revealed they get new information in every session. In conclusion, the use of MOOCs to support on-site classes is useful, but the use of technology, as a mean to learn, must be encouraged before applying online courses.